Does Pancasila Support Religious Pluralism in Indonesia in Postmodern Era - Philip Suciadi Chia; Frederich Oscar Lontoh; Surja Permana; Juanda Juanda; Daniel Ari Wibowo (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2019)
Since Indonesia is also one of the most diverse societies in the world such as there are over three hundred different ethnic groups in Indonesia, each with its own cultural identity, and more than two hundred and fifty distinct languages are spoken, then Pancasila is created as philosophic fundamentals of the state to supports the diversity in Indonesia. Pancasila (from a Sankrit word: panca: five and sila: principle) consists of five principles that are interrelated and inseparable to generate unity in diversity (bhinnekatunggalika). In this paper, I will argue that Pancasila promotesand facilitates religious diversity although religious culture in Indonesia does not promote religious pluralism.